Desperately Seeking Book Reviews: The Word of Mouth Marketing of South Korean Publishers and Booksellers. - Chekar, Choon Key (International Journal of the Book, 2008)
Online word of mouth is becoming an increasingly important and popular source of information that consumers can trust and rely on when making their decision to read or purchase a specific book. This paper examines the significance of online book reviews and book blogs as a platform of word of mouth marketing tool for both publishers and booksellers. By introducing some examples from South Korean book marketing campaigns using book-logs, this paper suggests that there are a great deal of benefits which are brought from using book-logs. However, we should not overlook the fact that there is also a risk that reader's non-commercial use of blogs could be hijacked by commercial interests.